Generalised Pythagorean fuzzy geometric interactive aggregation operators using Einstein operations and their application to decision making. Issue 6 (2nd November 2018) - Garg, Harish
Abstract : In this paper, we investigate the decision-making problem under the Pythagorean fuzzy environment by proposing some generalised aggregation operators. For it, we improve the existing aggregation operators by adding the pairs of the hesitation between the membership functions and hence proposed some new operational laws for Pythagorean fuzzy numbers using Einstein norm operations. Based on these laws, some weighted, ordered weighted and hybrid geometric interaction aggregation operators are proposed. The prominent characteristics of these operators are also studied. Further, a group decision-making problem is illustrated and validated through a numerical example. A comparative analysis of the proposed and existing studies is performed to show the validity of the proposed operators.